2021
DOI: 10.3390/foods10123002
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae as Sources of High-Quality Protein for Human Food and Protein Supplements

Abstract: As a result of population growth, an emerging middle-class, and a more health-conscious society concerned with overconsumption of fats and carbohydrates, dietary protein intake is on the rise. To address this rapid change in the food market, and the subsequent high demand for protein products, agriculture, aquaculture, and the food industry have been working actively in recent years to increase protein product output from both production and processing aspects. Dietary proteins derived from animal sources are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(73 citation statements)
references
References 129 publications
4
68
1
Order By: Relevance
“…The assessment of essential amino acids is vital when evaluating the nutritional value that a protein product can arrange. Various methods have been developed and used to assess the quality of the protein of a given product, for example, the composition of amino acids ( Table 2 ) and the score of these amino acids in comparison with the requirement standard proposed by the FAO/WHO ( Figure 2 ) [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The assessment of essential amino acids is vital when evaluating the nutritional value that a protein product can arrange. Various methods have been developed and used to assess the quality of the protein of a given product, for example, the composition of amino acids ( Table 2 ) and the score of these amino acids in comparison with the requirement standard proposed by the FAO/WHO ( Figure 2 ) [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Both the amount of protein and the protein quality are important. Microalgae are generally rich in proteins, and the protein content of microalgae varies between 20 and 60% of dry matter [166]. The quality of protein resources is usually described by different metrics taking into account factors as digestion, absorption and assimilation capacity.…”
Section: Discussionmentioning
confidence: 99%
“…The filamentous green algae Spirogyra and Oedogonium are used as a dietary component in Burma, Thailand, Vietnam, and India [204]. The earlier consumption of microalgae either directly or via incorporation into other food metrics was mainly to provide nutrients to people who were malnourished or in poverty, primarily to provide proteins while providing other nutrients as well, such as lipids and n-3 PUFA [211]. However, health benefits were not recognized until later, when research demonstrated their cellular and metabolic functions.…”
Section: Inclusion Of N-3 Pufa-rich Microalgae Biomass In Foodmentioning
confidence: 99%